Answer:
Step-by-step explanation:
First write it the shorter way. Leave out the middle term. What you have is the difference of squares.
a^2 - b^2 = (a + b)(a - b)
4x^2 - 9
(2x - 3)(2x + 3)
The answer is B
Answer:
the box
Step-by-step explanation:
what is x??
Hi there!
Answer:
x=-1
Step-by-step explanation:
Distributive property: ⇒ a(b+c)=ab+ac
5x-2=-7
add 2 both sides of an equation.
5x-2+-7+2
simplify.
5x=-5
divide by 5 both sides of an equation.
5x/5=-5/5
simplify
-5/5=-1
x=-1
Hope this helps!
-Charlie
Have a great day!
Answer:
YOU FORGOT REMAINDER
Step-by-step explana
8. True or false: in order to solve the following equation, you would first subtract by 4, then multiply by 5/1 *
4+1/5=-1
To solve 3x + 2 = 23 you must:
Subtract 2 from both sides so like this 3x+2−2=23−2 and get 3x=21.
Now Divide both sides by 3 so 3x/3=21/3. Mainly divide 21/3 and get 7.
--------------------------------------------------------------------------------
To solve -2y - 7 = 3 you must:
Add 7 to both sides so like this −2y−7+7=3+7 and get −2y=10.
Now Divide both sides by -2 so -2y/-2=10/-2. Mainly divide 10/-2 and get 5.
----------------------------------------------------------------------------------
False
Answer:
x = 4
Step-by-step explanation:
Subtract 2 from both sides. We get: 5x = 20.
Then x = 4